2021
DOI: 10.1371/journal.pone.0261614
|View full text |Cite
|
Sign up to set email alerts
|

Normal manual straight ahead pointing in Complex Regional Pain Syndrome

Abstract: There is evidence to suggest that people with Complex Regional Pain Syndrome (CRPS) can have altered body representations and spatial cognition. One way of studying these cognitive functions is through manual straight ahead (MSA) pointing, in which participants are required to point straight ahead of their perceived body midline without visual feedback of the hand. We therefore compared endpoint errors from MSA pointing between people with CRPS (n = 17) and matched controls (n = 18), and examined the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Investigations with patients in chronic upper limb pain have also shown a shift in perceived midline toward the affected side (Reinersmann et al, 2012). In studies comparing healthy participants and patients with CRPS, no significant difference was found in midline perception for tasks where participants pointed ahead with vision obstructed (Kolb et al, 2012;Verfaille et al, 2021;Vittersø et al, 2021) or directed an illuminated dot/rod to their perceived midline in light (Verfaille et al, 2021) and dark conditions (Verfaille et al, 2021;Wittayer et al, 2018). In contrast, participants with CRPS have also demonstrated a significantly larger leftward shift in their perceived midline compared to patients with chronic upper limb pain and healthy controls (Reinersmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations with patients in chronic upper limb pain have also shown a shift in perceived midline toward the affected side (Reinersmann et al, 2012). In studies comparing healthy participants and patients with CRPS, no significant difference was found in midline perception for tasks where participants pointed ahead with vision obstructed (Kolb et al, 2012;Verfaille et al, 2021;Vittersø et al, 2021) or directed an illuminated dot/rod to their perceived midline in light (Verfaille et al, 2021) and dark conditions (Verfaille et al, 2021;Wittayer et al, 2018). In contrast, participants with CRPS have also demonstrated a significantly larger leftward shift in their perceived midline compared to patients with chronic upper limb pain and healthy controls (Reinersmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of hand dominance may also play a role in this study's observed midline results. When asking participants to point straight ahead of their perceived body midline without visualising their hand, healthy controls made errors toward their dominant side when pointing with their dominant arm, and toward their non-dominant side when pointing with their non-dominant arm ( Vittersø et al, 2021 ). With the majority of participants in the current study right-hand dominant, this may explain the rightward midline bias observed in our study (and also the rightward bias in the majority of body landmarks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to compare the performance relative to the CRPS-affected versus unaffected side between the CRPS and control groups, we matched the non-dominant side of controls to the affected side of people with CRPS, following the approach used in previous studies. 26 , 30 A G*power 31 sample size calculation to detect a medium effect size ( eta 2 = 0.05) for an interaction between Group and Body Region (see “Statistical analyses” section), with an alpha level of 0.05 and 80% power resulted in a required sample size of 51, with 17 participants per group (UL-CRPS, LL-CRPS, controls). However, we fell slightly short of this recruitment target for the CRPS groups (see “Sample Characteristics” in the “Results” section).…”
Section: Methodsmentioning
confidence: 99%